2022
DOI: 10.3389/fimmu.2022.791267
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Infection and Cholesterol Metabolism

Abstract: Host cholesterol metabolism remodeling is significantly associated with the spread of human pathogenic coronaviruses, suggesting virus-host relationships could be affected by cholesterol-modifying drugs. Cholesterol has an important role in coronavirus entry, membrane fusion, and pathological syncytia formation, therefore cholesterol metabolic mechanisms may be promising drug targets for coronavirus infections. Moreover, cholesterol and its metabolizing enzymes or corresponding natural products exert antiviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 257 publications
1
24
0
Order By: Relevance
“…A redox imbalance can explain the individual variability of COVID-19. Coronaviruses exploit a host’s cholesterol metabolism to accommodate viral replication requirements and interfere with the host’s immune responses [ 41 ]. An in vitro study shows the inhibitory activity of the redox active oxysterol 27-hydroxycholesterol (27-HC) against SARS-CoV-2 without significant cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A redox imbalance can explain the individual variability of COVID-19. Coronaviruses exploit a host’s cholesterol metabolism to accommodate viral replication requirements and interfere with the host’s immune responses [ 41 ]. An in vitro study shows the inhibitory activity of the redox active oxysterol 27-hydroxycholesterol (27-HC) against SARS-CoV-2 without significant cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A strong relationship between cholesterol and coronavirus replication has been widely documented in the literature (Thorp and Gallagher, 2004;Syed et al, 2010;Heaton and Randall, 2011;Blanc et al, 2013;Del Campo and Romero-Goḿez, 2015;Guo et al, 2017;Meher et al, 2019;Lange et al, 2019;Cao et al, 2020;Radenkovic et al, 2020;Balgoma et al, 2020;Luquain-Costaz et al, 2020;Sanders et al, 2021;Cheng et al, 2021). Our previous study has also shown that cholesterol has an important role in coronavirus entry, membrane fusion and pathological syncytia formation; therefore cholesterol metabolic mechanisms may be promising drug targets for coronavirus infections (Dai et al, 2022). Herein, we obtained the gene expression profiles of DF-1 cells exposed to Dex for 24 h, and the RNA-seq data indicated that many genes associated with cholesterol biosynthesis were up-regulated by Dex.…”
Section: Discussionmentioning
confidence: 64%
“…Different papers reported that the virus is using the cholesterol to invade the cell. SARS-CoV-2 infection was also reported to cause lower serum cholesterol levels in COVID-19 patients (reviewed in 57 ). Our experiments demonstrate that pantethine reduces cellular cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%